PENERAPAN LKS MATA PELAJARAN AKUNTANSI DENGAN PENDEKATAN TUTORIAL PADA SISWA - Parjono, ; Sunarti, (Pendidikan Ekonomi, 2010)
The current study is to describe the use of accounting student-work sheet through tutorial approach for the eleventh graders of social science major at SMA Negeri 2 Magetan. The subjects were the eleventh graders of social science major in class 1 and 2. The data were collected with questionnaires and documentations. The data were then analyzed descriptively by dercribing, explaining, and exploring the the use of students work sheet and tutorial approach. The use of student-work sheets through the  tutorial approach was conducted in three meetings. The results show that the students responded positively to the use of the student-work sheet through tutorial approach.